85.1k views
4 votes
Find the solution to the following system using substitution or elimination:​

Find the solution to the following system using substitution or elimination:​-example-1
User Tessmore
by
4.8k points

2 Answers

3 votes

Answer:

D, -2, 1

Explanation:

Just got it correct on ap-x

User Cui Heng
by
4.7k points
3 votes

Answer:

D. (-2, 1).

Explanation:

y = 3x + 7

y = -2x - 3

AS the expressions on the right are both equal to y:

3x + 7 = -2x - 3

3x + 2x = -3 - 7

5x = -10

x = -2

Plug this into the first equation:

y = 3(-2) + 7

y = 1.

User Vikas Ojha
by
5.0k points